Bioethics, critical solidarity and organic volunteering - Selli, Lucilda; Garrafa, Volnei (Revista de Saúde Pública, 2005)
OBJECTIVE: The study proposes "critical solidarity" as a value to be incorporated into the 21st century's bioethics agenda and as an instrument to guide people and associations in volunteer praxis. METHODS: To explain how solidarity materializes itself, the motivations for engaging in volunteer activities in associations that integrate the corps of volunteers of the Instituto Nacional do Cancer [National Cancer Institute] in Rio de Janeiro, Brazil, are analyzed. The data for analysis were obtained by applying two instruments. The first one consists of a questionnaire divided into 2 parts: one part identifies the socioeconomic profile, and the other identifies solidarity as a value that motivates volunteer activity. The second instrument comprises of semi structured interviews utilized to collect supplementary data for analysis. RESULTS: The results indicate that volunteering is based on three basic motivations: a) personal motivations related to life as a volunteer, b) motivations resulting from professed beliefs, and c) motivations aroused by the feeling of solidarity. CONCLUSIONS: It was concluded that the incorporation of critical solidarity requires a rupture with the detected model of patronizing volunteering; it implies explicating the common selfish interests that permeate volunteer activities and qualify an organic volunteering, that is, volunteering which is politically aware and committed to responding to the specific demands of the present time.